Representations of the Gypsy in the Romantic Period - Houghton-Walker, Sarah (Oxford Univ. Press, 2014)
This publication examines the ways writers and artists from the Romantic period depict gypsies. It examines how various aspects of the contemporary context influence those depictions, and highlights the opportunities offered by the figure of the gypsy for the exploration of a range of hopes and fears Introduction – Background, histories, and myths: The situation of the Gypsies in the Romantic period – Literary contexts: The Gypsy and the page in the Romantic period – William Cowper's Gypsies – John Clare's Gypsies – Wandering, Wordsworth, and Gypsies – 'Place' in Austen's Emma: Englishness, Gypsies, and Harriet Smith – Aesthetic theories and literary traditions: Accommodating the Gypsy in art – Industry, idleness, and class – Conclusion
9780198719472
Keywords: Aufsatzsammlung; Romanticism; English literature; Romanies in literature; European literature